A non-catalytic in situ process to produce biodiesel from a rice milling by-product using a subcritical water-methanol mixture. (October 2017) - Zullaikah, Siti; Rahkadima, Yulia T.; Ju, Yi-Hsu
Abstract: A non-catalytic method to produce biodiesel in situ from a rice milling by-product, i.e. rice bran, using subcritical water-methanol mixture has been investigated. The method was found to be unaffected by initial moisture and free fatty acids (FFA) contents in rice bran so that no pretreatment was required. The yield and purity of biodiesel were higher under CO2 atmosphere than those under N2 atmosphere due the ability of the gas to acidify water-methanol mixture. Oil extraction from the bran was identified as the limiting step and complete oil extraction could be achieved in 3 h at 200 °C, 4 MPa (under CO2 atmosphere) and 43.8 wt% methanol concentration. Consequently, the highest biodiesel yield was also achieved at those operating conditions. The experimental data suggested that hydrolysis of rice bran oil into FFA followed by methyl-esterification of FFA into biodiesel could be the preferred reaction path to direct transesterification of oil. Subcritical water-methanol mixture was also able to break down complex carbohydrates in rice bran into simple sugars soluble in aqueous phase so that it could be separated easily from biodiesel. Highlights: A non-catalytic in situ process to produce biodiesel from rice bran was proposed. This method was unaffected by moisture and free fatty acids contents in rice bran. The use of CO2 as pressurizing gas increased biodiesel yield. Complex carbohydrates in rice bran were also broken down into simple sugars.